Developing standards to support the clinical translation of stem cells. (1st November 2021) - Cao, Jiani; Hao, Jie; Wang, Lei; Tan, Yuanqing; Tian, Yuchang; Li, Shiyu; Ma, Aijin; Fu, Boqiang; Dai, Jianwu; Zhai, Peijun; Xiang, Peng; Zhang, Yong; et al.
Abstract: Stem cells, which could be developed as starting or raw materials for cell therapy, hold tremendous promise for regenerative medicine. However, despite multiple fundamental and clinical studies, clinical translation of stem cells remains in the early stages. In contrast to traditional chemical drugs, cellular products are complex, and efficacy can be altered by culture conditions, suboptimal cell culture techniques, and prolonged passage such that translation of stem cells from bench to bedside involves not only scientific exploration but also normative issues. Establishing an integrated system of standards to support stem cell applications has great significance in efficient clinical translation. In recent years, regulators and the scientific community have recognized gaps in standardization and have begun to develop standards to support stem cell research and clinical translation. Here, we discuss the development of these standards, which support the translation of stem cell products into clinical therapy, and explore ongoing work to define current stem cell guidelines and standards. We also introduce general aspects of stem cell therapy and current international consensus on human pluripotent stem cells, discuss standardization of clinical‐grade stem cells, and propose a framework for establishing stem cell standards. Finally, we review ongoing development of international and Chinese standards supporting stem cell therapy. Abstract : Stem cell standard system. According to the requirements of stem cell preparation and evaluation, the standard system for stem cell clinical applications could include standards that cover the process management, quality of stem cell products, and the analytical method used for evaluation.